1987
DOI: 10.1002/j.1460-2075.1987.tb02729.x
|View full text |Cite
|
Sign up to set email alerts
|

Independent and synergistic activity of rol A, B and C loci in stimulating abnormal growth in plants

Abstract: The Ri plasmid A4 of Agrobacterium rhizogenes contains within its T‐DNA genetic information able to trigger root formation in infected plants. Tobacco plants regenerated from transformed roots display the hairy root (hr) syndrome. We show that DNA fragments containing the rol B locus alone are able to induce root formation both in tobacco and kalanchoe tissues. The rol A and the rol C loci by themselves are also able to induce root formation in tobacco but not in kalanchoe. This capacity to induce root formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
270
0
5

Year Published

1992
1992
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 409 publications
(285 citation statements)
references
References 38 publications
(38 reference statements)
7
270
0
5
Order By: Relevance
“…The plantlets were transformed with Agrobacterium tumefaciens strain GV3101 harboring the pPCV002-CaMVBT construct (rolB under the 35S Cauliflower mosaic virus promoter; Spena et al, 1987). The control nontransformed culture (R) was established from the same plantlets and cultivated under the same conditions as the transformed ones.…”
Section: Plant Cell Culturesmentioning
confidence: 99%
“…The plantlets were transformed with Agrobacterium tumefaciens strain GV3101 harboring the pPCV002-CaMVBT construct (rolB under the 35S Cauliflower mosaic virus promoter; Spena et al, 1987). The control nontransformed culture (R) was established from the same plantlets and cultivated under the same conditions as the transformed ones.…”
Section: Plant Cell Culturesmentioning
confidence: 99%
“…These plasmids contain the plant cassette vector pPCV002 [16] containing the gene of interest: rolC and rolB under cauli¯ower mosaic virus (CaMV) 35S promoter control and rolA under the control of its own 5' promoter [1]. Constructions also carry a gene for kanamycin resistance (NPT-II) under eukaryotic control sequences.…”
Section: Agrobacterium and Plasmidsmentioning
confidence: 99%
“…EcoRI 2225 bp fragment of pPCV002-CaMVBT was used as probe DNA for 1c-rolB culture. EcoRI 4480 bp fragment of pPCV002-ABC [1] was used as a probe for 1c-rolA culture.…”
Section: Dna Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently, changes in hormone level were thought to have a limited role in the formation of a hairy root tumor (5). A depends on the synergistic action of three genes called rolA, roiB, and rolC (18,21,22,27). Some experiments indicated that the rol genes, particularly rolB, act by increasing auxin sensitivity in transformed tissue (19,21).…”
mentioning
confidence: 99%